Predictive value of left atrial volumes assessed using real-time three-dimensional echocardiography for pulmonary hypertension in dogs with myxomatous mitral valve disease - Woo, In-Sun; Kim, Jung-Hyun (Frontiers in Veterinary Science, 2024)
Introduction Left atrial volume (LAV) obtained using real-time three-dimensional echocardiography (RT3DE) is an independent predictor of post-capillary pulmonary hypertension (PH) in humans; however, no studies have investigated LAV obtained using RT3DE as a predictor of post-capillary PH in dogs with myxomatous mitral valve disease (MMVD). Therefore, we aimed to evaluate the clinical applicability of LAV obtained using RT3DE compared to that obtained using two-dimensional echocardiography (2DE) in dogs with MMVD, with or without PH. Methods Medical records and echocardiographic images of 237 privately owned dogs with naturally occurring MMVD with or without PH were retrospectively reviewed. A total of 49 privately owned dogs with naturally occurring MMVD, with or without PH, were finally included (35 MMVD without PH, 14 MMVD with PH). The LAV and left ventricular volumes were obtained using 2DE and RT3DE. Echocardiographic parameters were analyzed to identify independent predictors of post-capillary PH. Results We found that the left atrial and left ventricular volumes obtained using 2DE and RT3DE indexed to body weight and several 2DE-derived variables were univariately associated with post-capillary PH. Furthermore, multivariable logistic regression analysis revealed that the RT3DE minimum LAV indexed to body weight (LAVi min) was the only significant independent predictor of post-capillary PH (odds ratio, 12.86; 95% confidence interval [CI], 2.40–68.99; p = 0.003), with the highest area under the curve value of 0.86 (95% CI, 0.75–0.96; p < 0.001). Discussion In conclusion, LAV indexed to body weight obtained using 2DE and RT3DE, can be a useful predictor of post-capillary PH in dogs with MMVD. In particular, the RT3DE LAVi min was observed to be the strongest predictor of post-capillary PH.